2019
DOI: 10.1021/acs.chemrestox.9b00299
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of N3-Methyl-2′-Deoxyadenosine in Nucleosome Core Particles

Abstract: N3-Methyl-2'-deoxyadenosine (MdA) is the major dA methylation product in duplex DNA. MdA blocks DNA replication and undergoes depurination at significantly higher rates than the native nucleotide from which it is derived. Recent reports on the effects of the nucleosome core particle (NCP) environment on the reactivity of N7-methyl-2'-deoxyguanosine (MdG) inspired this investigation concerning the reactivity of MdA in NCPs. NCPs containing MdA at selected positions were produced using a strategy in which the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…An AP site is one of the most abundant endogenous DNA lesions ( 2 ). It acts as an electrophile that can react with protein nucleophiles ( e.g., lysine and cysteine residues) to yield various types of covalent DPCs including Schiff base ( 16 , 17 , 18 , 22 , 24 , 25 , 45 , 46 ), thiazolidine ( 47 , 48 , 49 , 50 ), S -glycosidic ( 51 ), and N -glycosidic ( 52 , 53 ) bond-linked AP-protein adducts. These DPCs are either new types of DNA lesions or proposed to temporarily protect the lesions from the error-prone repair ( 17 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…An AP site is one of the most abundant endogenous DNA lesions ( 2 ). It acts as an electrophile that can react with protein nucleophiles ( e.g., lysine and cysteine residues) to yield various types of covalent DPCs including Schiff base ( 16 , 17 , 18 , 22 , 24 , 25 , 45 , 46 ), thiazolidine ( 47 , 48 , 49 , 50 ), S -glycosidic ( 51 ), and N -glycosidic ( 52 , 53 ) bond-linked AP-protein adducts. These DPCs are either new types of DNA lesions or proposed to temporarily protect the lesions from the error-prone repair ( 17 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the most concern among the different types of DNA crosslinks is the covalent linkage of DNA to proteins, which are known to pose adverse physiological effects in cells. , For example, the covalently bound DNA–protein cross-link (DPC) product 1 (see Figure ) was identified to originate from a lysine residue of human DNA polymerase β reacting with a 2-deoxyribonolactone unit found in a DNA molecule that suffered a C1′-oxidation damage, affecting the function of a key enzyme in the base excision repair machinery. Another example involved 8-oxo-dG, which is one of the most abundant oxidative stress-induced DNA lesions, being further converted to reactive species and coupled with histone proteins in nucleosome core particles to produce DPC 2 (see Figure ). It was also reported that DPCs 3 and 4 (see Figure ) were produced when methylating agent-induced apurinic/apyrimidinic (AP) sites in DNA condensed with lysine and cysteine residues in proteins of human cells. …”
mentioning
confidence: 97%
“…In contrast, reversible and specific noncovalent interactions of DNA with proteins, mediated by van der Waals forces, hydrogen bonding, and ionic interactions, are ubiquitous in all organisms and are fundamental to many biological processes, particularly in regulating gene expression, replication, repair, and transcription. Since the formation of covalently bound DPCs upon toxicant exposure would disrupt DNA–protein interactions that are part of normal cell physiology, they are extremely toxic. For example, DPCs can completely block DNA replication and transcription, and they can ultimately threaten genomic integrity and cell viability .…”
mentioning
confidence: 99%
See 2 more Smart Citations